2016
DOI: 10.1002/pi.5120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unsaturation in bicarboxylic acid dopants for solid‐state synthesis of polyaniline

Abstract: Conjugation in the polymeric backbone leads to an electrical conducting nature for conducting polymers, and organic acids can be used as dopants to manipulate the electroactive behaviour. The present investigation deals with the effect of unsaturation in bicarboxylic acid dopant structures on the properties of polyaniline (PAni). PAni was synthesized via solvent-free solid-state polymerization. Oxalic acid, fumaric acid and trans,trans-muconic acid containing 0, 1 and 2 double bonds, respectively, in their mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The electrochemical syntheses were carried out in a single compartment cell using aqueous solution of 0.1 M aniline sulfate and 0.5 M H 2 SO 4 . For electropolymerization, aniline sulfate was used instead of aniline because of its higher solubility in water which facilitates in rapid involvement in the synthesis process . Two types of PAni samples were prepared using (1) graphite plate (2 × 2 cm working area) as working electrode and Pt wire as counter electrode, and (2) NBR‐XC72 composite (2 × 2 cm working area) as both working and counter electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…The electrochemical syntheses were carried out in a single compartment cell using aqueous solution of 0.1 M aniline sulfate and 0.5 M H 2 SO 4 . For electropolymerization, aniline sulfate was used instead of aniline because of its higher solubility in water which facilitates in rapid involvement in the synthesis process . Two types of PAni samples were prepared using (1) graphite plate (2 × 2 cm working area) as working electrode and Pt wire as counter electrode, and (2) NBR‐XC72 composite (2 × 2 cm working area) as both working and counter electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…ANi polymerized by pressure polymerization in the presence of different dopants (such as HCl, H 2 SO 4 , H 3 PO 4 , methyl sulfonic acid, p‐toluene sulfonic acid and dodecylbenzene sulfonic acid) with APS [20,21] and oxalic acid, fumaric acid in H 2 SO 4 environment and in the presence of muconic acid dopants, with potassium peroxydisulfate (KPS), [22] In another study pressure polymerization was reported for ANi hydrochloride with FeCl 3 .6H 2 O [23] and silver nitrate [24] . Aniline hydrochloride was also polymerized by grinding in a mortar using different oxidants under 700 MPa [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous materials such as semiconductor, magnetic nanoparticle, metal oxide, carbon‐based nanomaterial, and intrinsically conducting polymer (ICP) have been developed for biosensing applications. Among the abovementioned material, ICP is much‐admired for biosensors due to its paramount characteristics such as biocompatibility, inimitable electronic structure (for facile transfer of electrons), tunable electrical conductivity (via doping), environmental stability, facile corrosion‐free synthesis, and sensitivity to small perturbations . Because of their efficient electron transfer capability, formed upon biochemical reactions, they have been comprehensively utilized as transducers in biosensor that forms an intermediary layer between the biological molecule and electronics that are used for signal readout.…”
Section: Introductionmentioning
confidence: 99%